Drift [videorecording (Blu-Ray)] - Farrell, Susanne; Maksik, Alexander, 1972-; Erivo, Cynthia, 1987-; Shawkat, Alia, 1989-; Ba, Ibrahima; Swinton Byrne, Honor, 1997-; Maksik, Alexander, 1972- (Utopia, 2024)
Jacqueline, a young refugee, lands alone and penniless on a Greek island, where she tries first to survive and then to cope with her past. While gathering her strength, she begins a friendship with a rootless tour-guide and together they find the resilience to forge ahead.